THE EXISTENCE OF PUBLIC SERVICE ENTITY ‘BADAN LAYANAN UMUM’ TO UNDERTAKE GOVERNMENTAL FUNCTION - Desak Putu Dewi Kasih (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2013)
ABSTRACTPublic Service Entity „Badan Layanan Umum‟ which is governed in the Governmental Regulation concerning the Financial Management of the Public Service Entity refers to any government institution which gives services to the public in the forms of products and/or services but benefit is not the main objective. It does its activities based on the principles of efficiency and productivity. The objective is to improve the services provided to the public as an attempt to increase the public welfare and to sharpen the nation‟s life. Finance is flexibly managed based on the principles of economy, productivity, and the application of healthy business practice. In short, the Public Service Entity does what the government is supposed to do when undertaking its serving functions.Keywords: Public Services, Public Service Entity, and Government Function